Soot formation characteristics in hybrid pyrolysis of zero-carbon fuel ammonia and ethylene mixtures - He, Jiaying; Ying, Yaoyao; Chen, Mingxiao; Liu, Dong (Frontiers in Energy Research, 2022)
As soot particles from incomplete combustion of fossil fuels pose a great threat to human health, the development of low-carbon or zero-carbon alternative fuels is essential to mitigate climate change. An experimental and numerical study on the pyrolysis properties of ammonia and ethylene mixtures is conducted, focusing on the properties of soot generated by pyrolysis under different conditions and the coupling relationship between soot properties and soot precursors. The results show that the graphitization degree of soot particles generated at higher pyrolysis temperatures is enhanced, but the oxidation reactivity is decreased. When ammonia is blended, the graphitization of soot decreases and the oxidation reactivity increases. The peak mole fractions of soot precursors are negatively correlated with the graphitization degree of soot particles as the temperature increases.